2014
DOI: 10.3390/ijms151120290
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 and Redox Status in Prediabetic and Diabetic Patients

Abstract: The redox status associated with nuclear factor erythroid 2-related factor-2 (Nrf2) was evaluated in prediabetic and diabetic subjects. Total antioxidant status (TAS) in plasma and erythrocytes, glutathione (GSH) and malondialdehyde (MDA) content and activity of antioxidant enzymes were measured as redox status markers in 259 controls, 111 prediabetics and 186 diabetic type 2 subjects. Nrf2 was measured in nuclear extract fractions from peripheral blood mononuclear cells (PBMC). Nrf2 levels were lower in predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 47 publications
(50 reference statements)
10
62
0
2
Order By: Relevance
“…It has been clinically demonstrated that there is a down-regulation of Nrf2 expression (mRNA and protein) in kidney biopsy [64], peripheral blood mononuclear cells (PBMC) [62,66] and skin tissue (foot ulcer and gangrene) in diabetics [67]. In fact, our group found decreased nuclear Nrf2 in PBMC obtained from prediabetics [66].…”
Section: Nrf2 In Prediabetes and Diabetesmentioning
confidence: 54%
See 1 more Smart Citation
“…It has been clinically demonstrated that there is a down-regulation of Nrf2 expression (mRNA and protein) in kidney biopsy [64], peripheral blood mononuclear cells (PBMC) [62,66] and skin tissue (foot ulcer and gangrene) in diabetics [67]. In fact, our group found decreased nuclear Nrf2 in PBMC obtained from prediabetics [66].…”
Section: Nrf2 In Prediabetes and Diabetesmentioning
confidence: 54%
“…In fact, our group found decreased nuclear Nrf2 in PBMC obtained from prediabetics [66]. Together, these studies have shown that Nrf2 down-regulation during chronic hyperglycemia could be an important target for treatment.…”
Section: Nrf2 In Prediabetes and Diabetesmentioning
confidence: 94%
“…Data were expressed as k/mg protein. SOD activity was determined by its ability to prevent formazan production from the reaction of NBT and superoxide anion (O ÁÀ 2 ) generated by the xanthine-xanthine oxidase system [41]. One hundred and fifty lg of mitochondrial protein or 50 mM phosphate buffer pH 7.0 (100 % formazan production) were added to the reaction mixture with the following composition: 90 lM xanthine, 16 mM Na 2 CO 3 , 2 mM KCN, 22.8 lM NBT, and 18 mM phosphate buffer; pH 7.0.…”
Section: Activity Of Antioxidant Enzymesmentioning
confidence: 99%
“…Studies, summarized in Table 5, show also that Type 2 DM is a condition of increased oxidative stress [44,45,103,[107][108][109].…”
Section: -Chloro-n-[2-[4-(cyclohexylcarbamoylsulfamoyl)mentioning
confidence: 99%